Industrial optical sorting for marine plastic litter management - A. Mendoza; G. Kortaberria; D. Carrero; A. Latorre; O.C. Basurko; C. Peña-Rodríguez (Waste Management Bulletin)
The aim of this study is to evaluate the possibility of incorporating marine litter from the coast into the management system of the non-selectively collected fraction of Municipal Solid Waste (MSW). With this purpose, the technical feasibility of automatic separation of marine plastic litter is evaluated, which would allow for subsequent recycling. This solution requires mechanical–biological-treatment plants (MBT) to be able to sort marine plastic litter. Poly (ethylene terephthalate) (PET) bottles constitute one of the most commonly reported types of marine plastics. Considering the sorting methods employed in MBT plants, optical sorting tests were performed with marine PET litter and compared with those for post-consumer municipal PET waste, in order to assess whether the current technology implemented in these plants would allow their automatic sorting. Results show that the separation efficiency of PET degraded under marine conditions and outdoors is very high, and close to that of post-consumer municipal PET waste. The separation efficiency by transparent colour for different types of PET materials evaluated is also very effective and similar to that obtained for separation by chemical composition. Therefore, the chemical differences observed would not affect the efficiency of automatic sorting of marine origin PET in a waste treatment plant.